Evaluation of agronomic variables and quality of sugarcane on different tillage practices - Vargas Díaz, Ruy (2023)
Soil conservation practices are a strategy to mitigate the constant degradation that can occur when crops are established. It is of great importance to evaluate the effect that this type of practices can have on the development of sugarcane plants. The objective of the study was to evaluate agronomic variables (population and stem weight, plant height and stem diameter) and quality of sugarcane juices (pH, content of soluble solids, reducing sugars, sucrose and phosphorus content) for panela production. For this, a one-factor experiment with two treatments (reduced and conventional tillage systems) was established in an area of 4000 square meters in the municipality of Vélez (department of Santander-Colombia). No statistically significant differences were observed (p > 0.05) in the evaluated variables, indicating that the evaluated tillage treatments do not interfere with both the development of the crop and the quality of the juices for panela production.